Development of an integrated and differentiated tahfidz teaching module to improve Quran memorization for students at MI Plus Al-Fatimah Sukorejo Bojonegoro - Mamlu’ah, Aya; Rohmawati, Ulva Badi’; Wahid, Najihah Binti Abdul (At- Ta'lim : Jurnal Pendidikan, 2024)
Teaching modules are independent curriculum frameworks that replace traditional lesson plans. The independent curriculum teaching module, which serves as a replacement for the RPP, has a diverse format that encompasses learning material/content, teaching methods, interpretation, and evaluation techniques. These modules are designed systematically and engagingly to meet the desired success indicators. The primary goal of developing teaching modules is to provide teachers with instructional tools that can guide them effectively in the teaching process. Teachers are given the autonomy to choose or modify the provided modules by the government to better match their students' characteristics or to create their own modules tailored to their students' needs. The developed teaching modules include integrated modules for tahfidz subjects at Madrasah Ibtidaiyah Plus Al-Fatimah, differentiated modules for tahfidz subjects at Madrasah Ibtidaiyah, guidelines for developing tahfidz teaching modules, instruments for developing these modules, and evaluation tools for assessing the module development process. This research and development (R&D) approach aims to create integrated and differentiated tahfidz teaching modules specifically for MI Plus Al-Fatimah. These modules cover the tahfidz teaching program, implementation guides, and evaluation instruments to assess the program's success. The development process involves the principal to ensure that students can achieve the target of memorizing four juz within six years at the madrasah ibtidaiyah level. The development stages include determining learning strategies and media, producing the modules, and creating assessment tools. This phased approach ensures that the integrated and differentiated tahfidz teaching modules are effective and meet the educational goals of the institution.